2004
DOI: 10.1038/sj.ijir.3901194
|View full text |Cite
|
Sign up to set email alerts
|

Clinical and sonographic assessment of the side effects of intracavernous injection of vasoactive substances

Abstract: The objective of this study is to evaluate the side effects of intracavernous vasoactive agents on clinical and sonographic basis. Two groups of patients were included, group I included 168 ED patients trained on self-injection therapy using one of the three protocols. Protocol A: papaverine; protocol B: PGE1; and protocol C: trimix (papaverine, phentolamine and PGE1). Patients were followed up clinically, sonographically and by laboratory investigations for 6 months to evaluate the occurrence of side effects.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
14
0
1

Year Published

2005
2005
2016
2016

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 28 publications
(16 citation statements)
references
References 10 publications
1
14
0
1
Order By: Relevance
“…It is noted that both side-effects occur with a higher incidence in the papaverine and papaverine/phentolamine groups versus the PGE1 and papaverine/phentolamine/ PGE1 groups. Further, the incidence of priapism is greater in the test dose versus that in the home dose, which is typical of the increased incidence of priapism occurring during the titration phase as reported in other studies [68,69]. Additionally, it has been shown that diabetics have an increased incidence of penile fibrosis, possibly owing to their microangiopathic disease and increased propensity for fibrosis [69].…”
Section: Intracavernosal Injectionsupporting
confidence: 51%
“…It is noted that both side-effects occur with a higher incidence in the papaverine and papaverine/phentolamine groups versus the PGE1 and papaverine/phentolamine/ PGE1 groups. Further, the incidence of priapism is greater in the test dose versus that in the home dose, which is typical of the increased incidence of priapism occurring during the titration phase as reported in other studies [68,69]. Additionally, it has been shown that diabetics have an increased incidence of penile fibrosis, possibly owing to their microangiopathic disease and increased propensity for fibrosis [69].…”
Section: Intracavernosal Injectionsupporting
confidence: 51%
“…25,26 Instead, we preferred the IIEF score that is a practical method in diagnosis due to its noninvasiveness and reproducibility. 13,14 In conclusion, ED has an increased prevalence in male patients with SCF compared to the control group.…”
Section: Discussionmentioning
confidence: 99%
“…All participants completed the IIEF questionnaire. According to questions 1-5 and 15 (six questions that form the so-called 'erectile function domain' 14 ) of the questionnaire, ED severity was classified into five categories as severe (1-10), moderate (11)(12)(13)(14)(15)(16), mild to moderate (17-21), mild (22)(23)(24)(25) and no ED (26)(27)(28)(29)(30) …”
Section: Sexual Function: International Index Of Erectile Functionmentioning
confidence: 99%
“…The most common cause of cavernosal fibrosis is repeated intracavernosal injection of papaverine and, less frequently, of prostaglandin E1 [12,[32][33][34] (Fig. 8).…”
Section: Postraumatic Scarring and Fibrosismentioning
confidence: 98%
“…At US segmental intracavernosal fibrosis is characterized by echogenic foci within the corpus cavernosum that show reduced expansion during erection [3,4,34]. The lesions are usually visible when the penis is flaccid, but they are more prominent with erection when the surrounding sinusoids are distended with blood.…”
Section: Postraumatic Scarring and Fibrosismentioning
confidence: 98%